Metronidazole loaded polycaprolactone-carbopol blends based biodegradable intrapocket dental film for local treatment of periodontitis - Dhedage N.; Khan G.; Ajmal G.; Kumar M.; Jha A.; Mishra B. (My University, 2025)
Objective: The goal of this research was to optimize and evaluate an intrapocket dental film, composed of polycaprolactone and carbopol blends for the management of periodontitis. Methods: The intrapocket dental film was prepared using a modified solvent casting method, followed by characterization, in-vitro release, in-vitro antimicrobial activity, and in-vivo efficacy on the periodontitis animal model. Result: Prepared films were consistent in thickness (2.10±0.56 to 2.50±0.39 mm) and weight (35.23±0.37 to 39.45±0.45 mg) with drug entrapment of up to 87.63±1.98 percent. The concentration of carbopol is observed to have a direct relationship with the thickness, film weight, and swelling factor of the prepared dental film. The film has a surface pH close to gingival crevicular fluid pH and is therefore appropriate for the application. The developed film exhibited a biphasic drug release profile with an initial burst release followed by a continuous release for more than 11 days. Drug release kinetic study supports the release of the drug by a diffusion-based process, as best explained by the Korsmeyer Peppas kinetics (R2 =0.9635). in vitro antimicrobial activity was also in accordance with drug release, with a high initial zone of inhibition (ZOI) (49.32±0.156mm), followed by 14.28±0.080 mm ZOI on the 11th day. The in vivo study showed that the prepared film was able to prevent periodontal ligament degeneration, as observed in the periodontitis experiment animal model. Conclusion: The prepared intrapocket dental film based on caprolactone and carbopol can be used as a novel local drug delivery system for the management of periodontitis. © 2021 Bentham Science Publishers.